Protocol for correlating the gut microbiome and metabolomics in patients with intracranial aneurysms - Hongyu Xu; Zetian Jia; Junhui Liu; Runming Liu; Wei Wei; Xiang Li (STAR Protocols)
Summary: Gut-microbiome-combined metabolomics studies in cerebrovascular disease highlight the microbiota-gut-brain axis in neurological disorders. Here, we present a protocol for correlating the gut microbiome and metabolomics in patients with intracranial aneurysms. We describe steps for sample collection, fecal genomic DNA extraction, rRNA PCR amplification, sequencing library construction, and rRNA sequencing. We then detail procedures for metabolite extraction, liquid chromatography-tandem mass spectrometry (LC-MS/MS) non-targeted metabolomics sequencing, and ELISA for cerebrospinal fluid and plasma samples. Finally, we perform combined multi-omics analysis.For complete details on the use and execution of this protocol, please refer to Xu et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.